THE EFFECT OF RADIATION ON THE TYROSINE SYSTEMS OF THE THYROID GLAND - Bahaa Hassoun Abbas; Nada Basheer (Academia Science Repository, 2023)
The thyroid takes iodine from blood circulation and absorbs it. The thyroid gland will absorb both stable (normal) and radioactive iodine since it is unable to distinguish between them. The thyroid gland is one of the most radiation-sensitive areas of the body in newborns and children. The most common treatment for thyroid cancer is radiotherapy. The goal of this study was to determine the thyroid gland's absorbed dose. The link between the absorbed dosage and thyroid hormone levels was also investigated. The mean thyroid dose was 2600 rad. Thyroid hormone levels did not alter significantly between pre-radiotherapy and post-radiotherapy. Increased thyroid absorbed dose and variations in TSH had a strong association. There was no evidence of a link between thyroid malfunction and age, gender, or chemotherapy treatment.